Competitiveness: A comparison of China and Mexico - Felicitas Nowak-Lehmann D.; Sebastian Vollmer; Inmaculada Martínez-Zarzoso (Center for Economic Studies and ifo Institute (CESifo), 2007)
Latin American countries have lost competitiveness in world markets in comparison to China over the last two decades. The main purpose of this study is to examine the causes of this development. To this end an augmented Ricardian model is estimated using panel data. The explanatory variables considered are productivity, unit labor costs, unit values, trade costs, price levels (in PPP), and real exchange rates in relative terms. Due to data restrictions, China's relative exports (to the US, Argentina, Japan, Korea, UK, Germany, and Spain) will be compared to Mexico's exports for a number of sectors over a period of eleven years. Panel and pooled estimation techniques (SUR-estimation, panel Feasible Generalized Least Squares (panel/pooled FGLS)) will be utilized to better control for country-specific effects (differences between American, Argentinian, Japanese, Korean, German, British, and Spanish markets), cross-section specific (sector-specific) effects, and correlation over time.
Keywords: C23; F11; F14; 330; Internationaler Wettbewerb; Komparativer Kostenvorteil; Vergleich; China; Mexiko